2022
DOI: 10.1108/ijbpa-11-2021-0157
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographical, geographical and climatological factors on building defects in Belgium

Abstract: PurposeQuality failures in the design and construction process can entail significant delays and costs. Databases of building defects have proven to be useful for drawing conclusions on underlying causes of building defects and for identifying potential improvement actions to reduce the occurrence of building defects.Design/methodology/approachThe database comprising 27,074 cases from a Belgian insurance company was studied, and it was found that moisture problems account for 48% of all building defects, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The papers of De Vos et al [8] and Van Deen Bossche et al [9] were based on a collection of building defects cases from 1991 to 2019, provided by the largest Belgian insurance company. The total amount of cases collected was 27,074, which were processed and filed by jurists or engineers.…”
Section: Insurance Company Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The papers of De Vos et al [8] and Van Deen Bossche et al [9] were based on a collection of building defects cases from 1991 to 2019, provided by the largest Belgian insurance company. The total amount of cases collected was 27,074, which were processed and filed by jurists or engineers.…”
Section: Insurance Company Databasementioning
confidence: 99%
“…To reduce costs, time, and emissions related to buildings, building defects need proper attention so that the stakeholders can gain important knowledge about the issue [6]. A better understanding of defect causes will form a base for improving the quality of buildings [7], thus it is important to gather building defect information systematically and to identify patterns and relations [8][9][10]. Today it is 2 possible to gain insight from a range of different building defect information sources if provided access to them, for example, by using machine learning and artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…The next contribution is entitled “The impact of demographical, geographical and climatological factors on building defects in Belgium” (Van Den Bossche et al , 2023), and authored by Nathan Van Den Bossche, Anke Blommaert and Bruno Daniotti. The authors argue that quality failures in the design and construction process can entail significant delays and costs.…”
Section: Description Of the Contributionsmentioning
confidence: 99%
“…Farrington et al [17] suggested that the width of the drainage channel between the evaluated silicone sealant applied at the exterior and pre-compressed foam tape applied at the interior should be at least 1 2 inch or 12.7 mm. On the other hand, a minimum cavity width of 10 mm is often prescribed for external walls, for example by the Canadian Building Code [39], as it is assumed that for this width, capillary effects will be diminished and that the largest portion of the infiltrated water will be drained along the inner side of the exterior barrier.…”
Section: A Single Layer Of Pre-compressed Foam Sealing Tapes Applied ...mentioning
confidence: 99%
“…Moisture problems are still the number one cause of damage to buildings, with infiltrated rainwater as the most important source of moisture in the building envelope [1]. Water infiltration often occurs at joints between different building envelope components such as joints between prefabricated façade elements or windows [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%